Interpreting Alexander Chayanov’s Peasant Utopia since 1991 - George, Lucian (Historia i Polityka, 2021)
Composed in 1919 as a rebuke to Bolshevik rule, Alexander Chayanov’s utopian story about a future, peasant-dominated Russia has fascinated scholars from a wide variety of disciplines. This article provides a critical overview of the Russian- and English-language scholarship on Chayanov’s peasant utopia that has emerged over the last three decades. The intellectual and ideological contexts in which the text has been situated are explored and compared. The article also discusses how the utopia has been understood in ideological and political terms, and how scholars have wrestled with ambiguities arising from its relativism, parodic qualities and potentially dystopian elements.